JENIS DAN KELIMPAHAN MIKROPLASTIK PADA AIR DI PANTAI MANGGAR KOTA BALIKPAPAN, KALIMANTAN TIMUR - Fibriana, Lisa; Ghitarina; Rafii, Akhmad (Jurnal Tropical Aquatic Sciences, 2024)
Marine debris is a major problem around the world. The most common type of marine debris is plastic waste. Plastic waste in the sea has various sizes, one of which is microplastic. The purpose of this study is to identify the types of microplastics in water at Manggar beach, analyze the abundance of microplastics in water at Manggar beach, and determine the comparison between types of microplastics in water at Manggar beach. Microplastic sampling was carried out in August 2022, at 1 station with a 100 meter transect line in Manggar beach waters using a plankton net with a mesh size of 0.18 µm. Destruction of organic matter from the sample using 30% H2O2 solution. The sample was then added with 0.05M FeSO4 solution. Identification of microplastics using olympus microscope microservice model CX21FS1 with 10x magnification. The results of the types of microplastics found in the research sampling locations are fragments, fibers and films. The highest abundance of microplastics was dominated by fragments (2,613.3 particles/L). The lowest microplastic abundance was the film type (538 particles/L). One-way anova test between microplastic types obtained a sig value of ρ0,000 < sig α0,05 which means H1 is accepted, indicating that there are significant differences between the types of film-fragment, fiber-film and fragment-fiber.